The immature stages of Smicridea (Rhyacophylax) gladiator Flint 1978 (Trichoptera: Hydropsychidae), with notes on distribution and bionomics - Desidério, Gleison Robson; Pes, Ana Maria; Hamada, Neusa; Nessimian, Jorge Luiz (Zootaxa, 2017)
Immature stages of many Brazilian Smicridea species remains unknown, and efforts to describe all life stages are required. In this paper, the larva and pupa of Smicridea (Rhyacophylax) gladiator Flint 1978, associated with adults through the metamorphotype method, are described and illustrated. In addition, the known distribution of this species is extended in the Brazilian Amazon Basin with new records from Amazonas state and the first record in Pará state. Information about its bionomics is also provided.